O Lugar do direito penal na luta dos movimentos de mulheres no Brasil - SOUZA, Luanna Tomaz de (Universidade do Estado do Rio de Janeiro, 2023)
The article analyzes the extent to which women's movements have used the use of criminal law as a mean of coping with the violence committed against women in Brazil and which are the problems arising from this linkage. First, we analyze the action of women's movements in Brazil, then the problems of recourse to the law in the actions of social movements and whether it can have an emancipatory bias. Finally, it is evaluated whether the action of the women's movements has imported a legitimation of a selective and violent system.